Anti-tumor effect of polysaccharide from Pleurotus ostreatus on H22 mouse Hepatoma ascites in-vivo and hepatocellular carcinoma in-vitro model - Kavish Hasnain Khinsar (SpringerOpen, 2021)
Abstract Hepatocellular carcinoma is one of the leading causes of cancer-associated death across the globe. Malignant ascites are the major clinical attributes in cancer patients. Despite the advancements in HCC treatments such as chemotherapy, radiotherapy, surgery, and hormonal therapy, researchers are pursuing novel natural edible compounds for the treatment of cancer to eliminate dreadful side effects. Pleurotus ostreatus is one of the most edible cuisines in Asia as well as all over the world. It has been a source of nutritious diet since it was classified as an edible mushroom with no or negligible side effects. The present study focused on the natural anti-cancerous and anti-ascites capabilities of polysaccharides extracted from Pleurotus ostreatus in-vivo as well as in-vitro. Administration of polysaccharide Pleurotus ostreatus showed a significant decrease in tumor cell metastasis while the increase in the survival period among mice models of H22 malignant ascites. Downregulation of regenerative genes Foxp3 and Stat3 and secretion of immunological factors such as IL-2, TNF α, and INF γ were observed after treating with the partially pure extracted polysaccharide. Twining with the hypothesis of tumor suppression in-vivo model polysaccharide showed a decrease in invasion and migration abilities and henceforth responsible for the gene regulation such Cytochrome C which supposedly induced the chain of gene regulation process resulting in apoptosis in HCC cell lines observed in-vitro experiments. Collective research findings manifested that polysaccharide extracted from Pleurotus ostreatus bears anti-proliferative activity and thus influence tumor suppression in-vivo and in-vitro against hepatocellular carcinoma and can be used for therapeutic purposes as a potential anti-cancerous source in the future.